PARTICIPATORY PLANNING IN REALIZING DEVELOPMENT IN SALUTAMBUNG VILLAGE, ULUMANDA DISTRICT, MAJENE REGENCY - Sari, Nurmala; Guntur, Muhammad; Johansyah, Oky Nur Pratiwi; Halim, Didin (Jurnal Aktor, 2025)
This study aims to determine Participatory Planning in realizing Development in Salutambung Village, Ulumanda District, Majene Regency. This type of research is qualitative with data collection techniques carried out by means of observation, interviews, and documentation. The data analysis technique used consisted of data reduction, data presentation and drawing conclusions. The results of the study show that participatory planning is based on indicators of participatory planning steps, so the researchers draw the conclusion that participatory planning in realizing development in Salutambung Village, Ulumanda District, Majene Regency, is good planning, which has involved the people of Salutambung Village in the process up to the budget planning process that has been mutually agreed upon. The recommendations from this study are that the Salutambung Village Government needs to pay more attention to and coordinate with all Village Officials so that all the community and can be involved in any activities that are known to be implemented such as the Musrenbang and other Coordination Meetings, as well as the community better increasing their involvement in the development planning process such as during Musrenbang activities and Coordination Meetings held by the local Government, because community involvement will make it easier to define and decide on development issues to be carried out.